2018
DOI: 10.1093/annonc/mdy253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of trabectedin in elderly patients with sarcoma: subgroup analysis from a phase III, randomized controlled study of trabectedin or dacarbazine in patients with advanced liposarcoma or leiomyosarcoma

Abstract: www.clinicaltrials.gov, NCT01343277.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…Once again, this finding is consistent with the subgroup analysis of the ET743-SAR-3007 trial, which showed comparable benefit and safety for trabectedin in patients aged ≥65 years. 27 One of the exploratory endpoints of this trial was to investigate the pharmacokinetics of trabectedin. To the best of our knowledge, this is the first study to specifically assess pharmacokinetics in such an elderly population.…”
Section: Figurementioning
confidence: 99%
“…Once again, this finding is consistent with the subgroup analysis of the ET743-SAR-3007 trial, which showed comparable benefit and safety for trabectedin in patients aged ≥65 years. 27 One of the exploratory endpoints of this trial was to investigate the pharmacokinetics of trabectedin. To the best of our knowledge, this is the first study to specifically assess pharmacokinetics in such an elderly population.…”
Section: Figurementioning
confidence: 99%
“…An age >65 years was associated with significantly higher hematological toxicity in a multivariate analysis. Moreover, investigators' general conservative approach in terms of increasing the rate of discontinuation due to drug-related AEs in treating elderly population cannot be ruled out as reported by some authors [28].…”
Section: Wide R0 Surgerymentioning
confidence: 98%
“…Outcome, safety, and tolerability of medical treatments in elderly patients with STS have been the subject of a series of retrospective subgroup analyses in clinical trials including all ages [27,28]. The invariable message of these analyses was that the elderly population has similar outcomes when compared with younger ones when active treatments are employed at the cost of an augmented toxicity that would require an age customization schedule and a careful selection of patients.…”
Section: Wide R0 Surgerymentioning
confidence: 99%
“…Furthermore, the safety profile for elderly patients treated with trabectedin was similar to that in the overall study population treated with trabectedin. 93…”
Section: Treatment For Rpss With Elderly Patientsmentioning
confidence: 99%